Corona again? SSC after a severe COVID-disease - Arnstadt, Benno; Zillinger, Christian; Treitl, Marcus; Allescher, Hans-Dieter (Zeitschrift für Gastroenterologie, 2021)
Secondary sclerosing cholangitis (SSC) is a severe complication of intensive care treatment in critically ill patients. It is characterized by rapid onset and severe chlolestasis with elevation of gGT. In contrast to primary sclerosing cholangitis, SSC-CIP has a distinct and timely well defined trigger and can have a rapid progress to cirrhosis and liver failure. In context of the COVID-19-pandemic, there are reports about patients, who developed SSC after a severe COVID-infection and intensive care treatment.We report on a 62-year old patient without any relevant pre-existing illnesses, who suffered from severe COVID-19 pneumonia with the need for long term ventilation. In the course of the disease he developed a critical-illness-polyneuropathy a pronounced cholestasis. After recovery from COVID-pneumonia, the PNP regressed but the cholestasis progressed. MRCP showed only irregular intrahepatic bile ducts, while EUS showed echogenic intraductal longitudinal structures characteristic for intraductal casts and for SSC-CIP. This was confirmed with ERC, where the complete necrotic bile ducts could be extracted and retrieved for histological and molecular analysis.The patient was included in a scheduled ERC-program to prevent a progress of SSC and the concomitant cirrhosis.SSC is an often missed diagnosis, which obviously can also occur in COVID-patients. In case of elevated liver function tests with cholestasis, EUS might be the key diagnostic method to characterize intraductal casts and identify those patients who should undergo ERC.
Keywords: Leber; Secondary Sclerosing Cholangitis; COVID19